Formation of spin-polarized current in antiferromagnetic polymer spintronic field-effect transistors. Issue 42 (20th October 2022) - Sun, Shih-Jye; Menšík, Miroslav; Ganzorig, Chimed; Toman, Petr; Pfleger, Jiří
Abstract : Gate-controlled spin-polarized current is formed intrinsically in a spintronic FET based on an antiferromagnetic polymer chain. Abstract : We have theoretically investigated the feasibility of constructing a spintronic field-effect transistor with the active channel made of a polymer chain with the antiferromagnetic coupling oriented in the source-to-drain direction. We found two different device function regimes controlling the on-chain spin–charge carrier density by tuning the gate voltage. At higher charge carrier densities, the source–drain current linearly increases with decreasing charge carrier densities. In this regime, no polymer spin-polarized current is observed. Upon reaching a critical gate voltage, the current decreases with decreasing charge densities. It is accompanied by the formation of spin-polarized current, generated by an on-chain process, which can be related to spin–charge spatial distribution symmetry breaking caused either by an application of the source-to-drain voltage (higher spin polarization near the drain), or the breakdown of the Peierls dimerization near chain ends. Numerical simulation of the transistor characteristics suggests that the design of a polymer spintronic field-effect transistor is in principle feasible.